Social comparison on social media and mental health: A scoping review - Arenz, Anisha; Meier, Adrian; Reinecke, Leonard (Beiträge zur Jahrestagung der Fachgruppe Rezeptions- und Wirkungsforschung 2022, 2023)
Social media offer their users a variety of opportunities for online self-presentation and thus represent an optimal environment for social comparisons. With the increasing popularity of social media, there is growing concern in public and scientific discourse about negative effects of online social comparisons on users’ mental health. Research output on this topic is increasing rapidly, making the field more heterogeneous and difficult to oversee. This scoping review therefore aims to provide a systematic mapping of the fragmented research field on social media comparisons and mental health. Using predefined inclusion criteria, 131 quantitative studies were systematically identified to map the research field. The results showed that the number of studies has grown since 2011 and that first authors from the United States and Psychology departments were the main contributors. With regard to the comparison directions, comparison dimensions, and indicators of mental health examined, the analyses demonstrate that the studies primarily focused on upward comparisons on diverse dimensions and hedonic well-being, whereas downward comparisons and other facets of mental health are currently under-represented in the fiel